The Effect of The Class of Champion Learning Model with Wordwall on Critical Thinking Skills of Grade 3 Students - Syahrani, Meisya Dea; Utami, Ratnasari Diah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Learning innovations that enhance critical thinking are needed because third-grade students at Trosemi 02 Public Elementary School have difficulty understanding mathematical ideas. The objective of this study is to determine the application of the Wordwall app, which is used in Clash of postts learning, and its effect on the critical reasoning skills of third-grade students at Trosemi 02 Public Elementary School. Methodology: The research design used quantitative methods with a pre-experimental single-group pretest-posttest procedure. Using total sampling, 14 students were selected as research subjects. Tests, documentation, interviews, and observations were some of the methods used for data collection. Using SPSS software version 22, the data were examined using a paired sample t-test as well as validity, reliability, and normality tests. Results: The results of the study indicate that the use of Wordwall with the Clash of Champions learning model has a significant impact on pupils' capacity for critical thought. The average pretest score of 73.37 rose to 85.06 on the posttest, with a significant value (Sig. 2-tailed) of 0.000 < 0.05. Applications/Originality/Value: Using Wordwall in conjunction with the Clash of Champions model has the potential to be an interactive teaching strategy that enhances students' critical thinking abilities. By incorporating game-based digital media into competitive learning activities, these findings offer a novel approach to learning that is applicable in the context of contemporary education.